ANALISIS KEUNTUNGAN USAHA INDUSTRI KACANG SANGRAI FEBRI DI DESA KANONANG 3 KECAMATAN KAWANGKOAN INDUK (Analysis of Business Profit of Sangrai Febri Industry in Kanonang Village 3 Kawangkoan Induk Sub District) - Olivia Rawis; Grace A. J. Rumagit; Joachim N. K. Dumais (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2020)
The objective of this research is  to analyze the business profit of the Sangrai Febri  Industry business in Kanonang 3 Village, Kawangkoan Induk Sub District. This research has been conducted for  three months, from April to June 2018. Data that will be used in this study are primary data Primary data is data obtained by researchers in the field directly from the source, namely in this study is the owner of the Febri roasted bean business. Data collection techniques used in research is observation and interviewed by using questionnaire.            The research results of this study indicated the revenue  received by the sangrai bean business is Rp. 700,000, total costs of Rp.510,405.48 and profits of Rp.189,594.52. Thus, Febri's roasted bean business is profitable.  Keywords: Business Benefits, Febri Sangrai Beans